Knowledge and Perception Related to Telepharmacy Utilization Among Pharmacist Professional Students in Central Java, Indonesia: A Cross-Sectional Study - Sulistyaningrum, Indriyati Hadi; Arfianto, Erki; Pasyah, Kurnia; Pribadi, Prasojo; Sari, Seftika (Sciences of Pharmacy, 2026)
This cross-sectional study examined the association between knowledge and perception and telepharmacy utilization among pharmacy professional students in Central Java, Indonesia. A purposive sample (n = 219) completed a validated questionnaire. Data were analyzed using the Chi-square test to assess associations between variables. The results showed that 75.8% of respondents had high knowledge and 96.8% had positive perceptions; however, only 36.1% reported telepharmacy utilization. A statistically significant association was found between knowledge and telepharmacy utilization (χ² = 5.62, p = 0.018, Cramer’s V = 0.16), indicating a small effect size. In contrast, perception was not significantly associated with telepharmacy utilization (p = 0.451). These findings suggest that knowledge may be related to telepharmacy utilization among students. However, due to the cross-sectional design, causal relationships cannot be established. Limitations of this study include non-probability sampling, self-reported data, and potential response bias. Further research with more robust designs is recommended.